Melatonin regulates gene expressions through activating auxin synthesis and signaling pathways - Wei, Wei; Tao, Jian-Jun; Yin, Cui-Cui; Chen, Shou-Yi; Zhang, Jin-Song; Zhang, Wan-Ke (Frontiers in Plant Science, 2022)
Both melatonin and indole-3-acetic acid (IAA) are derived from tryptophan. And the most interesting and unsolved puzzle in melatonin research is that what is the relationship between melatonin and auxin? In this study, we performed transcriptome analysis with a time series method to disclose the connection of the two metabolites in soybean. Our results reveal that melatonin and IAA treatments cause substantial overlaps in gene expression changes. Common genes of melatonin and IAA treatments could be sorted into clusters with very similar expression tendency. A KEGG assay showed that exogenous applied melatonin enriched differentially expressed genes in auxin biosynthesis and signaling pathways. For details, melatonin up-regulates several YUCCA genes which participate in auxin biosynthesis; melatonin also enhances expression levels of auxin receptor coding genes, such as TIR1, AFB3 and AFB5; dozens of genes involved in auxin transport, such as AUXI and PIN, are regulated by melatonin similarly as by auxin; auxin-responsive genes, such as IAA, ARF, GH3 and SAUR-like genes, intensively respond to melatonin as well as to auxin. A DR5 promoter mediated GUS staining assay showed that low concentration of melatonin could induce auxin biosynthesis in a dosage manner, whereas high concentration of melatonin would eliminate such effect. At last, gene ontology (GO) analysis suggests that melatonin treatment has similar characteristics as auxin treatment in many processes. However, the two molecules still keep their own features respectively. For example, melatonin takes part in stress responses, while IAA treatment enriches the GO terms that related to cell growth. Taken together, exogenous applied melatonin, if not exceeds the appropriate concentration, could promote auxin responses range from biosynthesis to signaling transduction. Thus, our research is a key part to explain the auxin-like roles of melatonin in regulating plant growth.